Overview Of Personal Hygiene And Health Complaints To The Garbage Carrier Officer At The TPS Medan Sunggal District - Syahrani, Putri; Azzahra, Fatimah; Nasution, Dinda Azria; Lestari, Ninis; Hazrin, Yosita; Arrazy, Syafran (P3M Universitas 'Aisyiyah Surakarta, 2025)
Background: Waste haulers are at high risk of various diseases due to direct contact with waste. Good personal hygiene is very important to prevent diseas. This research aims to identify personal hygiene practices and health complaints of waste transport workers at TPS Medan Sunggal District. Methods: This research uses a qualitative approach with in-depth interviews, observation and documentation. Key informants and supporters were selected based on length of service. Results: The research results show that the majority of officers have not implemented optimal personal hygiene practices. Personal Protective Equipment (PPE) is not used optimally when working, maintaining personal hygiene such as washing hands with soap and using gloves is not done consistently. Several officers experienced health complaints of skin disorders, such as irritation of the scalp and itching of the hands. Conclusion: Lack of awareness of waste transport officers and inadequate facilities such as no hand washing facilities are the main factors causing the lack of implementation of personal hygiene among waste transport officers. Training needs to be carried out regarding the importance of personal hygiene, providing adequate facilities, socialization, and enforcing discipline to increase awareness and compliance of officers in maintaining personal hygiene.